Hemorrhage risk of direct oral anticoagulants in real-world venous thromboembolism patients. Issue 204 (August 2021) - Jin, Michael C.; Sussman, Eric S.; Feng, Austin Y.; Han, Summer S.; Skirboll, Stephen L.; Berube, Caroline; Ratliff, John K.
Abstract: Introduction: Venous thromboembolism (VTE) management increasingly involves anticoagulation with direct oral anticoagulants (DOACs). Few studies have used competing-risks analyses to ascertain the mortality-adjusted hemorrhage and recurrent VTE (rVTE) risk of individual DOACs. Furthermore, hemorrhage risk factors in patients treated with apixaban remain underexplored. Materials and methods: Patients diagnosed with VTE receiving anticoagulation were identified from the Optum Clinformatics Data Mart (2003–2019). Study endpoints included readmissions for intracranial hemorrhage (ICH), non-intracranial hemorrhage (non-ICH hemorrhage), and rVTE. Coarsened exact matching was used to balance baseline clinical characteristics. Complication incidence was evaluated using a competing-risks framework. We additionally modeled hemorrhage risk in apixaban-treated patients. Results: Overall, 225, 559 patients were included, of whom 34, 201 received apixaban and 46, 007 received rivaroxaban. Compared to rivaroxaban, apixaban was associated with decreased non-ICH hemorrhage (sHR = 0.560, 95%CI = 0.423–0.741), but not ICH, and rVTE (sHR = 0.802, 95%CI = 0.651–0.988) risk. This was primarily in emergent readmissions (sHR[emergent hemorrhage] = 0.515, 95%CI = 0.372–0.711; sHR[emergent rVTE] = 0.636, 95%CI = 0.488–0.830). Contributors to emergent hemorrhage in apixaban-treated patients include older age (sHR = 1.025, 95%CI = 1.011–1.039), female sex (sHR = 1.662, 95%CI = 1.252–2.207), prior prescription antiplatelet therapy (sHR = 1.591, 95%CI = 1.130–2.241), and complicated hypertension (sHR = 1.936, 95%CI = 1.134–3.307). Patients anticipated to be "high-risk" experienced elevated ICH (sHR = 3.396, 95%CI = 1.375–8.388) and non-ICH hemorrhage (sHR = 3.683, 95%CI = 2.957–4.588) incidence. Conclusions: In patients with VTE receiving anticoagulation, apixaban was associated with reduced non-ICH hemorrhage and rVTE risk, compared to rivaroxaban. Risk reduction was restricted to emergent readmissions. We present a risk-stratification approach to predict hemorrhage in patients receiving apixaban, potentially guiding future clinical decision-making. Highlights: Apixaban may be associated with decreased ECH, but not ICH, risk (vs rivaroxaban). Apixaban may reduce emergency readmissions for recurrent VTE compared to rivaroxaban. We developed a model to anticipate hemorrhage risk during apixaban anticoagulation.